A volunteer computing system implemented with peer-to-peer communication optimized for small and limited environments - Santiago, Caio; Digiampietri, Luciano Antonio (Anais do Brazilian e-Science Workshop (BreSci), 2018)
The computational needs of scientific experiments often require powerful computers. One alternative way to obtain this processing power is taking advantage of the idle processing of personal computers as volunteers. This technique is known as volunteer computing and has great potential in helping scientists. However, there are several issues which can reduce the efficiency of this approach when applied to complex scientific experiments, such as, the ones with long processing time, very large input or output data, etc. In order to face these challenges, we designed a volunteer computing system based on peer-to-peer communication. When compared with the local execution of activities and traditional volunteer computing, the execution time was improved and, in some cases, there was also a reduction of the server upload bandwidth use.